2020
DOI: 10.3390/s20185074
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Reliability of SmartWatch to Obtain 3-Lead Electrocardiogram Recordings

Abstract: Some of the recently released smartwatch products feature a single-lead electrocardiogram (ECG) recording capability. The reliability of obtaining 3-lead ECG with smartwatches is yet to be confirmed in a large study. This study aimed to assess the feasibility and reliability of smartwatch to obtain 3-lead ECG recordings, the classical Einthoven ECG leads I-III compared to standard ECG. To record lead I, the watch was worn on the left wrist and the right index finger was placed on the digital crown for 30 s. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Proprietary technologies already allow direct recording and interpretation of an ECG tracing from a smartwatch [ 93 ]. For example, the Kardia Band used an Apple smartwatch to detect possible AF from intermittent PPG registrations, with user wrist haptic/buzz notification to record an ECG from the band, followed by an automated ECG interpretation [ 94 ], but this device is no longer available.…”
Section: Opportunities For New Digital Technologies To Overcome Barriers In Screening Diagnosis and Monitoring For Afmentioning
confidence: 99%
“…Proprietary technologies already allow direct recording and interpretation of an ECG tracing from a smartwatch [ 93 ]. For example, the Kardia Band used an Apple smartwatch to detect possible AF from intermittent PPG registrations, with user wrist haptic/buzz notification to record an ECG from the band, followed by an automated ECG interpretation [ 94 ], but this device is no longer available.…”
Section: Opportunities For New Digital Technologies To Overcome Barriers In Screening Diagnosis and Monitoring For Afmentioning
confidence: 99%
“…In the current study, we included only adult participants with sinus rhythm to validate SW-ECG precordial leads. However, in the other studies the focus was either on pediatric patients, or on the accuracy of SWs to capture cardiac arrhythmias such as atrial fibrillation in adults, the feasibility of obtaining the Einthoven leads I-III, and the ability of handheld devices to detect ST-segment changes [ 6 , 7 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study investigating the performance of handheld ECG devices to detect atrial fibrillation in a geriatric ward and a cardiology ward found that in 21.4% of the elderly patients in the geriatric ward, a recording with a handheld device could not be performed, while in the cardiology ward with younger patients, it was only 7% [ 21 ]. In another study by our research group, we found that patients had no problems with recording Einthoven leads I-III with a SW by themselves after a short training [ 10 ]. We assumed that it is more difficult for patients to record the precordial leads by themselves and position the SW at the right location than to record lead I-III, which only needs positioning of the SW on the wrist and the lower abdomen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The positioning of the Apple Watch Series 4 for obtaining leads I, II, and III using the Einthoven triangle. In the Apple Watch, the negative electrode is placed in the digital crown and the positive electrode is on the back crystal of the watch [ 15 ]. …”
Section: Methodsmentioning
confidence: 99%